An Analysis of Public- and Private-Sector Wages Allowing for Endogenous Choices of Both Government and Union Status - Gyourko, Joseph; Tracy, Joseph (Journal of Labor Economics, 1988)
A general selection model is estimated in which workers select across four labor markets-private/nonunion, privat e/union, public/nonunion, and public/union. Evidence is found of posi tive selection bias in the private/nonunion sector and of negative se lection bias in the public/union sector. Union wage differentials in the public and private sectors as well as public/private wage differe ntials are contrasted. The authors discuss when it is appropriate to use each type of differential. Copyright 1988 by University of Chicago Press.